Paraglottic Space Invasion in Glottic Laryngeal Cancer: A Clinical‐Pathological Study. (6th August 2022) - Fermi, Matteo; Lo Manto, Alfredo; Di Massa, Gianluca; Gallo, Graziana; Lupi, Massimo; Maiolo, Vincenzo; Montrone, Grazia; Lovato, Luigi; Presutti, Livio; Mattioli, Francesco
Abstract : Objective: This study aims to prospectively compare endoscopic, radiological, and pathological features of a cohort of patients with glottic laryngeal squamous cell carcinoma (LSCC) undergoing open partial horizontal laryngectomy (OPHL) type II/III or total laryngectomy to better understand the reliability of preoperative endoscopy and computed tomography (CT) to predict the inferior paraglottic space (iPGS) involvement. Methods: We prospectively compared the endoscopic, radiological, and pathological findings in patients with glottic LSCC who underwent OPHL II/III, or total laryngectomy. Results: Endoscopy achieved a diagnostic accuracy of 87.2% for the anterior iPGS (iPGSa) and 86.1% for the posterior iPGS (iPGSp). There was no statistically significant difference in terms of histopathologic iPGSa involvement between reduced (85%—17/20 pts) and absent (92%—24/26 pts) vocal cord mobility ( p = 0.39). CT alone did not improve the diagnostic performance of the endoscopy, reaching a diagnostic accuracy of 62.9% and 73.7% for the iPGSa and iPGSp, respectively. When endoscopy and CT were combined, the diagnostic performance improved for the iPGSp, achieving a sensitivity (Se), specificity (Spe), positive predictive value (PPV), and negative predictive value (NPV) of 100%, 89.8%, 68.7%, and 100%, respectively. On the contrary, the combination of CT and endoscopy improved only the Se and NPV for the iPGSa with respect to the sole endoscopic assessment. Conclusions: Whenever motility impairment is present, a histopathologic invasion of the iPGS should be suspected. Endoscopic assessment of laryngeal motility achieved a satisfactory value of Se, Spe, PPV, and NPV in predicting the involvement of the iPGS. CT scan is still the mainstay imaging technique in the clinical staging of patients with LSCC. Level of Evidence: 4 Laryngoscope, 133:1184–1190, 2023 Abstract : To prospectively compare endoscopic, radiologic, and pathologic features of a cohort of patients with laryngeal squamous cell carcinoma undergoing open partial horizontal laryngectomy type II/III or total laryngectomy at a tertiary‐care academic center in order to better understand the reliability of preoperative endoscopy and computed tomography to predict the iPGS involvement.